THE TEACHING STRATEGY FOR TEACHING ENGLISH GUIDANCE AND COUNCELING BY USING FACEBOOK GROUP IN INDONESIA - Angga Taufan Dayu (Intensive Journal, 2018)
This study try to explore the benefits of Facebook in teaching English in an Indonesia college.  The aims of the study are to discuss the kinds of language teaching and learning activities via Facebook, the use of Facebook in facilitating the teaching and learning in English for guidance counselling area. The data draws in descriptive design. The tool of collecting data is interview. The findings indicate that reading, writing and discussion activities can be held via Facebook and all of the participants agreed that Facebook helps them in learning English. The contribution of the study is to enhance a better understanding  to  use  of  Facebook  as  an  alternative  tool  can be  used  for teaching and learning.  The ultimate goal of study is to enhance students ‘interactions outside the classroom. By using Facebook students can get to know sharpen education to its highest level and made it more interesting, therefore creating good learning environments.